SIMULASI SLINGSHOOT: APLIKASI UNTUK MENINGKATKAN PEMAHAMAN KONSEP GERAK PARABOLI BAGI SISWA SMA - Wulansari, Septi; Oktamaypasha, Rias; Setiaji, Bayu (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
Science and technology have developed rapidly due to globalization. Almost everyone now has a mobile phone. Therefore the research uses the flexibility of mobile phones that will be implemented to create an application design that will become a means of learning for students. This research aim is to test the feasibility of the design of the Slingshot Simulation application as a learning medium to increase students' conceptual understanding of parabolic motion material. This study uses the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. However, the authors limit this research only to the application design stage and then analyze the feasibility validation of the application design by one expert appraiser, two practitioner appraisers, and twenty-seven limited trial respondents. From the results of the feasibility validation of the application design, an average result of 94.53% is obtained. In a sense, the sling shoot simulation application design is feasible to be developed for use.